Critical damping of structures with elastically supported visco-elastic dampers. - Lee, Yujin (Earthquake engineering & structural dynamics.)
This paper presents a new formulation for critical damping of structures with elastically supported visco-elastic dampers. Owing to the great dependence of damper performance on the support stiffness, this model is inevitable of reliable modelling of structures with visco-elastic dampers. It is shown that the governing equation of free vibration of this model is reduced to a third order differential equation and the conventional method for defining the critical damping for second order differential equations cannot be applied to the present model. It is demonstrated that the region of overdamped vibration is finite in contrast to that (semi-infinite) for second order differential equations and multiple critical damping coefficients exist. However, it turns out that the smaller one is practically meaningful.